2018
DOI: 10.1186/s13229-018-0204-x
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR/Cas9-induced shank3b mutant zebrafish display autism-like behaviors

Abstract: BackgroundHuman genetic and genomic studies have supported a strong causal role of SHANK3 deficiency in autism spectrum disorder (ASD). However, the molecular mechanism underlying SHANK3 deficiency resulting in ASD is not fully understood. Recently, the zebrafish has become an attractive organism to model ASD because of its high efficiency of genetic manipulation and robust behavioral phenotypes. The orthologous gene to human SHANK3 is duplicated in the zebrafish genome and has two homologs, shank3a and shank3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
111
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 127 publications
(124 citation statements)
references
References 46 publications
(69 reference statements)
12
111
0
1
Order By: Relevance
“…Shank3b mutants (shank3b -/-) showed no obvious developmental or behavioral deficits upon superficial inspection as adults, consistent with previous observations (Liu et al, 2018). To confirm that shank3b mutants nevertheless showed altered responses to sensory input we first analyzed the behavior of freely swimming adult zebrafish towards a movie of conspecifics ( Figure 5A).…”
Section: Perturbation Of Visuomotor Mismatch Signals By a Mutation Insupporting
confidence: 86%
See 2 more Smart Citations
“…Shank3b mutants (shank3b -/-) showed no obvious developmental or behavioral deficits upon superficial inspection as adults, consistent with previous observations (Liu et al, 2018). To confirm that shank3b mutants nevertheless showed altered responses to sensory input we first analyzed the behavior of freely swimming adult zebrafish towards a movie of conspecifics ( Figure 5A).…”
Section: Perturbation Of Visuomotor Mismatch Signals By a Mutation Insupporting
confidence: 86%
“…These fish showed an enhanced attraction to movies of conspecifics that was phenocopied by the overexpression of the dominant-negative shank3b isoform shank3b ΔC , indicating that specific effects on behavior were caused by the disruption of shank3b function. Consistent with this conclusion, a previous study reported that a mutation in shank3b resulted in reduced social interactions and enhanced repetitive behaviors in adult zebrafish (Liu et al, 2018).…”
Section: Aberrant Processing Of Prediction Errors In Shank3b -/Fishsupporting
confidence: 78%
See 1 more Smart Citation
“…Like in rodents, disruption of some ASD-related genes provokes ARB-like phenotypes in zebrafish. For example, SHANK3 knockout zebrafish display aberrant circling, thigmotaxis, corner-tocorner swimming and 'looped' figure-8 swimming [105]. With high homology of SHANK3 between rodents and zebrafish (Table 2), such fish ARBs resemble stereotypies in mouse mutants of this gene [106][107][108].…”
Section: Autism-related Modelsmentioning
confidence: 99%
“…Albeit potentially reflecting increased anxietylike behavior in some contexts (e.g., anxiogenic center avoidance), this response may also represent a pathological repetitive behavior (e.g., evoked by psychostimulants, such as nicotine) relevant to stereotypic peripheral hyperlocomotion, commonly seen in rodents (e.g., following psychostimulant drugs) Selected examples of genetic models of aberrant repetitive behaviors in zebrafish.SHANK3 (left panel)is an autism-related gene that encodes postsynaptic density protein (PSD, binding to glutamatergic NMDA receptors) whose ablation in mice impairs synaptic transmission. Knockdown of SHANK in zebrafish up-regulates NMDA receptor and evokes ARB-like repetitive circling, corner-to-corner and figure-8 swimming (top view), according to[105]. A synaptic ras GTPase-activating protein SYNGAP1 (right panel) is another key protein involved in synaptic transmission, whose hypofunction in mice induces precocious maturation of synapses and increases synaptic transmission.NMDA receptor interact with postsynaptic density-95 (PSD-95) protein, which binds to SYNGAP.…”
mentioning
confidence: 99%